PENGARUH CASH POSITION, DEBT TO EQUITY RATIO, RETURN ON ASSETS, GROWTH, DAN FIRM SIZE TERHADAP DIVIDEND PAYOUT RATIO - Nurfi Ainush Shofa, 10.05.52.0151; Indarti, MG Kentris (Students Journal of Accounting and Banking, 2015)
This study aims to determine the influence analysis cash position, debt-to-equity ratio, return on assets, growth, firm size and dividend payout ratio.The populationin this studyis a manufacturing company that is listed on the Indonesia Stock Exchange 2011-2013.Â The samples used in this study are listed Manufacturing Company in Indonesia Stock Exchange period 2011-2013. The samples in study were taken by Pooled Data. The samples used by 146 companies.Data were analyzed by using the Ordinary Least Square (OLS) regression.Â The results showed cash position has no effect on the DPR, DER significant positive effect on the DPR, ROA significant positive effect on the DPR, growth has no effect on the DPR, and firm size significant positive effect on the DPR.Keywords: DPR, Cash Position, DER, ROA, Growth, Firm Size